2013 IEEE 4th International Conference on Cognitive Infocommunications (CogInfoCom) 2013
DOI: 10.1109/coginfocom.2013.6719230
|View full text |Cite
|
Sign up to set email alerts
|

Increasing communication between a man and a dog

Abstract: International audienceIn this paper, we present the first results we have concerning our ongoing work on a robotic system embedded on a dog to enrich communication. Two problems are addressed here: How to keep control of a dog when the human does not see it? For dog trained to do some specific activities in particular situation, how to detect this activity? We present here results on controlling the dog by an embedded voice and a real-time recognition of some activities of the dog : walk, seat, run, lying

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Golbeck and Neustaedter (2012) and Neustaedter and Golbeck (2013) explored and evaluated the use of pet-based video chat systems to facilitate remote monitoring and correspondence between pet owners and their dogs. Wearable technologies have been developed to assist remote verbal communication between owners and companions (Lemasson et al 2013), and in-person communication between working dogs and handlers (Jackson et al 2013). In the latter, the authors found that working dogs could successfully activate wearable electronics based on biting, tugging, and nose gestures to correspond with handlers.…”
Section: Introductionmentioning
confidence: 99%
“…Golbeck and Neustaedter (2012) and Neustaedter and Golbeck (2013) explored and evaluated the use of pet-based video chat systems to facilitate remote monitoring and correspondence between pet owners and their dogs. Wearable technologies have been developed to assist remote verbal communication between owners and companions (Lemasson et al 2013), and in-person communication between working dogs and handlers (Jackson et al 2013). In the latter, the authors found that working dogs could successfully activate wearable electronics based on biting, tugging, and nose gestures to correspond with handlers.…”
Section: Introductionmentioning
confidence: 99%
“…For each utterance, a count is made of tokens shared with immediately preceding turns for each speaker -the speaker's own last turn (6) and each interlocutor's last turn (5), in each case determined by (4) for the each n of the n−grams. These are repetition counts.…”
Section: Methodsmentioning
confidence: 99%
“…Research has designed interactions to enrich farm animals' physical and mental well-being [28], as well as adapted existing digital technology for captive zoo animals to increase public engagement and understanding [113] by allowing zoo visitors to observe animals interacting with technology familiar to them. Extensive work has also been done on the design of digital technology for working animals [6,43], and the adaption of existing digital technology and algorithms to increase the relationship between humans and their pets [53,58,78,81]. As a result, research on animal-centered technology has built an extensive understanding of how technology might serve animals and the people they interact with.…”
Section: Background and Motivation-the Need For An Information Systems Perspectivementioning
confidence: 99%